1999
DOI: 10.1002/(sici)1096-8628(19990820)88:4<337::aid-ajmg9>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Follow‐up study on a susceptibility locus for schizophrenia on chromosome 6q

Abstract: Evidence for suggestive linkage to schizophrenia with chromosome 6q markers was previously reported from a two-stage approach. Using nonparametric affected sib pairs (ASP) methods, nominal p-values of 0.00018 and 0.00095 were obtained in the screening (81 ASPs; 63 independent) and the replication (109 ASPs; 87 independent) data sets, respectively. Here, we report a follow-up study of this 50cM 6q region using 12 microsatellite markers to test for linkage to schizophrenia. We increased the replication sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 8 publications
(12 reference statements)
2
44
0
Order By: Relevance
“…Subsequent finemapping analysis of these regional findings, conducted at the Australian Genome Research Facility, provided support for the initial findings on chromosomes 2 and 10 [57]. To follow up the original 6q linkage finding by Pablo Gejman (Northwestern University, Chicago), we are collaborating with his group on linkage [70] and candidate gene studies [71][72][73] in this region. In addition, our group has continued to contribute to methodological issues [59,60,45] and to the analysis of the field's most prominent hot-spot regions both separately [62][63][64], and as part of multi-site collaborative analyses, including the investigation of defined chromosomal regions on 22q [65], 3p, 6p and 8p [66], Xp [67], on 5q, 6q, 10p and 13q [52] and more recently on 1q [68] and 22q [69].…”
Section: Independent and Collaborative Molecular Genetic Analysesmentioning
confidence: 82%
“…Subsequent finemapping analysis of these regional findings, conducted at the Australian Genome Research Facility, provided support for the initial findings on chromosomes 2 and 10 [57]. To follow up the original 6q linkage finding by Pablo Gejman (Northwestern University, Chicago), we are collaborating with his group on linkage [70] and candidate gene studies [71][72][73] in this region. In addition, our group has continued to contribute to methodological issues [59,60,45] and to the analysis of the field's most prominent hot-spot regions both separately [62][63][64], and as part of multi-site collaborative analyses, including the investigation of defined chromosomal regions on 22q [65], 3p, 6p and 8p [66], Xp [67], on 5q, 6q, 10p and 13q [52] and more recently on 1q [68] and 22q [69].…”
Section: Independent and Collaborative Molecular Genetic Analysesmentioning
confidence: 82%
“…This study is unique in that a second independent sample of families held by the same researchers was used to replicate the finding internally, and supported the results from the first sample. A further replication study by the same group found positive but less significant maxima in a third independent sample (Martinez et al, 1999). Combining the data from both replication samples, an interval of ~8 Mb gave the strongest results under both parametric and nonparametric approaches, with a LOD of 3.82 and highly significant excess allele sharing.…”
Section: Chromosome 6q21-q22 Linkage Studiesmentioning
confidence: 88%
“…The CB1R gene is located in human chromosome 6q14-q15, and it is interesting that previous reports showed evidence for possible linkage to schizophrenia with chromosome 6q markers (Martinez et al, 1999). In addition, evidence exists for a schizophrenia susceptibility locus on chromosome 6q (Cao et al, 1997).…”
Section: Polymorphic Structure Of Cannabinoid Receptor Genesmentioning
confidence: 99%